Standard Protection for the Human Genome - Mutair, Mahdi; Abdul Ameer, Husam (Journal of Legal Sciences, 2023)
The legal protection of the human genome is an ethical issue related to the future of human existence. After the disclosure of the human genetic map, scientific practices and research related to the human genome increased, especially the negative applications of genetic engineering that violates basic human rights, especially the right to human dignity, and pose real challenges to the existence and diversity of Present and future generations. Therefore, the existence of legal rules at the national and international levels is an absolute necessity to prohibit these threats and to arrange civil and criminal liability for those who violate them.